E-Shops Integration Opportunities with Courier Organisations in Bulgaria - Dragomirov, Nikolay (Research Papers, 2020)
The growth of e-commerce worldwide is a sustainable process. E-commerce processes are possible by the e-commerce platforms that are specialized software solutions that manage relationships with the other supply chain members, including the logistics service providers. Particular interest are the opportunities to integrate these platforms with the courier organizations for enabling the delivery process, where a number of refinement alternatives can be found.
Keywords: Logistics; E-commerce; Courier organisations